Effectiveness Behavioral Coating with Modeling Techniques and Assertive Training Techniques to Increase Confidence - Lailatul Fitriyah; Nyoman Dantes; Luh Putu Sri Lestari (Bisma The Journal of Counseling, 2017)
This study aims to understand: Effectiveness of behavioral counseling techniques of modeling and assertive training techniques to improve students' self-confidence. The experimental design used was Nonequevalen Control Group Design, this study included "quasieksperimen" research. The population of this study is the students of class X Boga SMK Negeri 2 Singaraja which amounted to 203 people. The sample was taken using purposive sampling technique with 16 students who have low self esteem by obtaining low score, as many as 8 people assigned as experimental group 1 and 8 the rest are assigned as experiment group 2. Data collection was confident in this study using a self-confident questionnaire. The results showed that there are differences in the effectiveness of students who follow Behavioral Counseling modeling techniques and students who follow assertive training techniques to improve students' self confidence X grade Boga SMK N 2 Singaraja.